Synthesis, Characterization and Biological Activity of Novel 1,3,4-Oxadiazole Derivatives of 1,3-Dihydro-1-oxoisobenzofuran-5-carboxylic Acid - Rao, Nunna Madhava; Viveka, Tella Lakshmi; Raju, Koneti Mallikarjuna; Chary, Maringanti Thirumala (Asian Journal of Chemistry, 2019)
This work relates to the synthesis of novel 1,3,4-oxadiazole derivatives (5a-h) from 1,3-dihydro-1-oxoisobenzofuran-5-carboxylic acid. The structure of the synthesized compounds were confirmed by using IR, 1H NMR, 13C NMR and mass spectroscopy. Further these synthesized derivatives were subjected to biological activity.